Preferred Frame Effects in Propagation of Cosmic and Gamma Rays - Georgy I. Burde (New Frontiers in Physical Science Research Vol. 8, 2023)
In this paper, the ’relativity with a preferred frame’, designed to reconcile the relativity principle with the existence of the cosmological preferred frame, is applied to electromagnetic phenomena and particle physics used to study propagation of cosmic and gamma rays in the framework of the theory. The new finding include: the modified electromagnetic field equations; modified electromagnetic wave theory and its observational consequences (such as the birefringence of light propagating in vacuo and dispersion); new features in the spectra of cosmic and gamma rays propagating through the background radiation from distant sources to Earth (such as a dependence of the threshold values for pion photoproduction by cosmic rays and pair production by gamma-rays on the distance to the source); a new mechanism of reducing or suppression of the electromagnetic cascades development by the preferred frame effects.